Integrated Marketing Communication Strategy in New Student Admissions Through Recognition of Past Learning (RPL) at the Graduate Faculty of Fajar University - Mujahid; Andi Vita Sukmarini; Abdul Samad A (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
his study aims to analyze the integrated marketing communication strategy as well as the inhibiting and supporting factors of the integrated marketing communication strategy in the admission of new students through the recognition of past learning at the Graduate Faculty of Fajar University. The approach used in this study is a qualitative approach with a descriptive research strategy. This research was carried out at the Faculty of Postgraduate Studies of Fajar University which was carried out from October to November 2024. The informants of this research are 7 informants, namely, the coordinator of Past Learning Recognition, the Vice Dean of Postgraduate Fajar University, the Head of the Master of Communication Studies Study Program, the Head of the Master of Management Study Program, RPL students from Batches 1, 2, 3 and 4 2 people each. The results of this study show that the strategy carried out by the Faculty of Postgraduate Strategy to get new students, especially the RPL program, includes several steps, namely through advertising, social media, promotion, publicity, official website, in addition to cooperation with relevant institutions or companies is also carried out to facilitate the process of introducing and disseminating information about this program. Furthermore, the development of alumni networks through the RPL program can be an effective marketing tool because their direct experience can increase the attractiveness of the program for students. Supporting factors in the admission of new students through the recognition of past learning are the existence of an organizer's permit from LLDikti and the Ministry of Education, Research and Technology, Accreditation from Fajar University and the Study Program has been accredited B, tuition fees can be paid in installments, and good service from the entire academic community of Fajar University, especially at the Postgraduate Faculty. Meanwhile, the inhibiting factors are the limitation of human resources in the Postgraduate Faculty, the long distance when the final project exam will be held, the lack of socialization carried out by the Postgraduate on the part of the Regional Government, and the need for follow-up for the regions that have been visited by the University.